BIG Data - BIG Gains? Understanding the Link Between Big Data Analytics and Innovation - Thomas Niebel; Fabienne Rasel; Steffen Viete (International Telecommunications Society (ITS), 2017)
This paper analyzes the relationship between firms' use of big data analytics and their innovative performance for product innovations. Since big data technologies provide new data information practices, they create new decision-making possibilities, which firms can use to realize innovations. Applying German firm-level data we find suggestive evidence that big data analytics matters for the likelihood of becoming a product innovator as well as the market success of the firms' product innovations. The regression analysis reveals that firms which make use of big data have a higher likelihood of realizing product innovations as well as a higher innovation intensity. Interestingly, the results are of equal magnitude in the manufacturing and services industries. The results support the view that big data analytics have the potential to enable innovation.
Keywords: D22; L20; O33; 330; Big data; data-driven decision-making; innovation; product innovation; firmlevel data